Reflections on the population and development agenda for Latin America and the Caribbean beyond 2014 (UN ECLAC SantiagoCL, 2012)
Sets out reflections for devising a population and development agenda for the region beyond 2014. Puts the spotlight on some of the region's cross-cutting population and development issues and identifies factors to be weighed when devising agreements, goals, policies and mechanisms for following up the agenda.
Keywords: POPULATION